Evaluasi program latihan berpidato dalam membentuk karakter berani dan kemampuan berkomunikasi pada santri - Amiruddin; Syaifudin; Thahir, Andi (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2022)
This study aims to see how this speech training program works. This research is focused on Pondok Modern Darussalam Gontor Campus 7 Kalianda South Lampung using a goal oriented evaluation model. The method used in this study is a qualitative research method with an evaluation research design by conducting observations, interviews, and reviewing program implementation documents. Sources of information were obtained through interviews with speech training program supervisors, speech training program supervisors, and students. The results of the research on the evaluated components indicate that the goal oriented of Pondok Modern Darussalam Gontor Campus 7 Kalianda South Lampung has been successfully implemented. It can be seen from the existing planning, organization, implementation, and control. However, there are also some students who still have not mastered the content of their speech and the intonation when giving a speech is also still lacking.